2014
DOI: 10.1039/c3cy01004j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2crystal structure on the catalytic performance of Co3O4/TiO2catalyst for low-temperature CO oxidation

Abstract: Co3O4 supported on TiO2 (anatase (A), rutile (R) and P25 (Degussa)) catalysts were prepared by a deposition–precipitation method. Co3O4/TiO2 (A) shows excellent activity for CO oxidation with 100% conversion at −43 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(82 citation statements)
references
References 61 publications
7
67
1
3
Order By: Relevance
“…It can be seen that main peaks of Co 3 þ 2p 3/2 and Co 3 þ 2p 1/2 are shown at binding energies of $ 779.6 and $ 795.1 eV, respectively. The energy difference between the Co2p 3/2 peak and the Co2p 1/2 peak is approximately 15 eV [30]. Those of Co 2 þ 2p 3/2 and Co 2 þ 2p 1/2 are located at $ 781.1 and $ 795.7 eV, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…It can be seen that main peaks of Co 3 þ 2p 3/2 and Co 3 þ 2p 1/2 are shown at binding energies of $ 779.6 and $ 795.1 eV, respectively. The energy difference between the Co2p 3/2 peak and the Co2p 1/2 peak is approximately 15 eV [30]. Those of Co 2 þ 2p 3/2 and Co 2 þ 2p 1/2 are located at $ 781.1 and $ 795.7 eV, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…It is found that the TiO 2 decorated Co 3 O 4 nanocomposite shows a much better sensing performance than the pristine Co 3 O 4 NW arrays. 2 ) have already been discussed in detail in a previous study. 29 Aer stirring for 20 min, the homogeneous solution was transferred into a 100 ml Teon lined stainless steel autoclave.…”
Section: 20mentioning
confidence: 92%
“…12 As we know, designing a heterojunction structure between different band gap and energy level semiconducting materials is an effective way to enhance the photocatalytic and catalytic activity, and gas sensing performance of the nanocomposite material. 2,[22][23][24] Recently, it has been found that designing a p-n junction by combining Co 3 O 4 with other n-type semiconductors would be a signicant route to enhance its gas response. 12,[25][26][27][28] In the heterogeneous region, the p-type semiconductor Co 3 O 4 and the n-type semiconductor TiO 2 can form a self-built electric eld, and establish a depletion layer.…”
Section: 20mentioning
confidence: 99%
See 1 more Smart Citation
“…In Fig. 3(b), the peaks at 780.2 and 781.8 eV can be attributed to Co 3+ and Co 2+ , respectively [53,54]. The peaks at 786.3 and 804.8 eV are considered as the shake-up satellite peaks of Co 2+ [54].…”
Section: Characterization Of MCCmentioning
confidence: 94%